Placental Chorangiosis: Clinical Risk Factors and Pregnancy Outcomes - Nada Alayed; Maria A. Arafah; Waleed H. Alkhamis; Khalid Akkour; Ghada A. AlMalki; Munerah A. M. Alomari; Lama Alshwairikh; Ahmed Sherif Abdel Hamid (Clinical and Experimental Obstetrics & Gynecology)
Background: Placental chorangiosis is a response to fetal hypoxia, linked to be associated with maternal/fetal disorders and higher mortality rates. Therefore, this study aimed to explore the association of placental chorangiosis with specific maternal clinical risk factors, as well as its impact on pregnancy outcomes compared to pregnancies with normal placental conditions. Methods: This retrospective case-control study was conducted at King Saud University Medical City (KSUMC) between September 2018 and December 2021. A total of 78 pregnant women were included, and 26 cases of placental chorangiosis were identified and included in the study, which were randomly matched to 52 controls. The demographic data of maternal factors (age, body mass index (BMI), type of gestation, gravidity, and parity) and pregnancy outcomes (abortion, gestation age at delivery, mode of delivery, born alive or not, Appearance, Pulse, Grimace, Activity, and Respiration (APGAR) score at 1 and 5 minutes, birth weight, and mean placental weight) were retrieved from the patient’s medical records, all placental histopathological examination were reviewed. Simple and multiple logistic regression analysis were used, and crude and adjusted odds ratios (ORs) and relative risk (RR) were reported with a 95% confidence interval (95% CI). Results: None of the potential maternal risk factors (age, BMI, type of gestation, gravidity, and parity) were statistically associated with chorangiosis. Chorangiosis, however, exhibit statistically significant associations with an increased number of abortions (RR: 21.59, 95% CI: 1.24–376.20, p = 0.003), intrauterine fetal death (IUFD; RR: 4.50, 95% CI: 1.53–13.25, p = 0.004), and low neonatal APGAR scores at 5 minutes (RR: 3.31, 95% CI: 1.22–9.01, p = 0.029). Conclusion: Placental chorangiosis is a rare pathological change in the placenta resulting from the interaction of several maternal and fetal disorders. When present, it can serve as an important indicator of chronic fetal hypoxia and predict poor obstetrical outcomes.